Condensation regulation of packaged strawberries under fluctuating storage temperature. Issue 11 (25th July 2019) - Bovi, Graziele G.; Caleb, Oluwafemi J.; Rauh, Cornelia; Mahajan, Pramod V.
Abstract : Disruption in cold chain during distribution and retail could have a significant impact on in‐package condensation of optimally designed packaged fresh produce. The aim of this work was to regulate in‐package condensation and evaluate the performance of different packaging design systems for strawberries under fluctuating temperatures (between 10°C and 20°C) for 5 days. The design included the use of condensation control strategies, namely, enhanced permeable films (NatureFlex and Xtend) and FruitPad of different fructose content (0%, 20%, 30%, 35%, and 40%). Package performance was evaluated in terms of headspace gas composition, mass loss, condensation, physico‐chemical changes, and visual and ortho‐nasal quality evaluation. Percentage mass loss of packaged strawberries ranged from 0.6% to 4% and was 33% for unpackaged. Results also showed that compared with the control sample, both strategies (enhanced permeable films and FruitPads) were effective in reducing condensation. In addition, transpirational water loss, results of the water absorbed by the FruitPads and transferred through the films were used to understand the packaging design needs under fluctuating temperature. Abstract : Compared with the control sample, both strategies (enhanced permeable films and FruitPads) were effective in reducing condensation under fluctuatinf temperature.